The determinants of corporate governance disclosure level in the integrated reporting context - Filippo Vitolla; Nicola Raimo; Michele Rubino (8th OFEL (Organizational, Financial, Ethical and Legal Issues) conference on Governance, Management and Entrepreneurship, “From corporations to social entrepreneurs: exploring the different faces of social innovation”, April 17-18 2020, Dubrovnik, Croatia, 2020)
In recent years, the analysis of corporate governance aspects is becoming a central element for understanding corporate dynamics and represents a clear indicator of investor confidence in the decisions taken by the management and board of listed firms. For this reason, corporate governance disclosure is receiving more and more attention from both a professional and academic point of view. The advent of integrated reporting represents a new tool for disclosing information relating to corporate governance. The goal of this study is to investigate the factors that can influence the level of corporate governance disclosure within the integrated reports. The analysis, conducted on a sample of 73 international firms, shows a positive effect of the firm size, firm profitability and audit quality. To our knowledge, this is the first study that analyses corporate governance disclosure level in the integrated reporting context
Keywords: 330; corporate governance; disclosure; integrated reporting; information quality